Provision of Bilingual Dispensing Labels to Non-Native English Speakers: An Exploratory Study - Helena Herrera; Murtada Alsaif; Ghalib Khan; Nicola Barnes; Paul Rutter (MDPI AG, 2019)
Patients with limited English proficiency living in the U.K. receive prescribed medication labels in English. These patients are at risk of worse health outcomes compared with the general population. This article describes a service evaluation of the use of bilingual dispensing labels to facilitate patient understanding of medicine administration instructions. Recruited patients answered two questionnaires to assess engagement with and understanding of their medicine labels. The first was completed at the point of dispensing, and the second within six weeks. Questionnaires were either self-completed or via facilitation over the telephone. A total of 151 participants completed the first questionnaire, and 130 completed the follow-up. Key findings highlighted the lack of engagement by participants with English-language labels and their reliance on asking for help from pharmacy staff, friends, or family to understand the information. However, when provided with information in their preferred language, they reported high levels of understanding and sought help less frequently from a third party. This study has shown that this service has improved understanding of labelling information in this target group.